2013
DOI: 10.1007/s12013-012-9508-1
|View full text |Cite
|
Sign up to set email alerts
|

Northeast Red Beans Produce a Thermostable and pH-Stable Defensin-Like Peptide with Potent Antifungal Activity

Abstract: A 5.4-kDa antifungal peptide was purified from Phaseolus vulgaris L. cv. "northeast red bean" using a protocol that entailed affinity chromatography, ion exchange chromatography, and gel filtration. The molecular mass was determined by matrix-assisted laser desorption ionization time-of-flight. The N-terminal amino acid sequence of the peptide was highly homologous to defensins and defensin-like peptides from several plant species. The peptide impeded the growth of a number of pathogenic fungi, including Mycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Another study showed that an antimicrobial protein derived from Bacillus subtilis FB123, named BSAMP, was highly thermostable after treatment at 100°C; its antimicrobial activity did not change [23]. Northeast red beans produce thermostable and pH-stable defensin-like peptides that fully maintain their antimicrobial activity at temperatures as high as 100°C and at pH values ranging from 0 to 12 [24]. The apparent stability of these peptides following exposure to heat or different pH values could potentially be attributed to their ability to promote in vitro aggregation of the acidic phospholipid dimyristoylphosphatidylserine or interactions that result in a reduction to their cationic charges [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that an antimicrobial protein derived from Bacillus subtilis FB123, named BSAMP, was highly thermostable after treatment at 100°C; its antimicrobial activity did not change [23]. Northeast red beans produce thermostable and pH-stable defensin-like peptides that fully maintain their antimicrobial activity at temperatures as high as 100°C and at pH values ranging from 0 to 12 [24]. The apparent stability of these peptides following exposure to heat or different pH values could potentially be attributed to their ability to promote in vitro aggregation of the acidic phospholipid dimyristoylphosphatidylserine or interactions that result in a reduction to their cationic charges [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several other plant defensins with antifungal activity have also been studied. Specific information about some of those defensins can be found on the following references: Medicago sativa defensin 1 ( Ms Def1) and Medicago truncatula defensin 4 ( Mt Def4; Spelbrink et al, 2004; Ramamoorthy et al, 2007a,b; Sagaram et al, 2011); Dahlia merckii AMP 1 ( Dm AMP1; Thevissen et al, 1999, 2000a,b, 2003b; Jha et al, 2009; Salahinejad et al, 2013); Phaseolus vulgaris defensin 1 ( Pv D1; Games et al, 2008; Mello et al, 2011; Wu et al, 2011; Chan et al, 2012; Wong et al, 2012; Chan and Ng, 2013); Nicotiana alata defensin 1 ( Na D1; Lay et al, 2003, 2012; van der Weerden et al, 2008, 2010; Hayes et al, 2013). …”
Section: Recently Studied Antifungal Defensinsmentioning
confidence: 99%
“…Research on common bean proteins have been focused on the antioxidant capacity of hydrolysates and their potential for ACE inhibition, metal chelation, and NF‐κB suppressor activity (Oseguera‐Toledo and others ; Carrasco‐Castilla and others ; Valdez‐Ortiz and others ; Rui and others ), antitumor activity (Chan and others ; Luna‐Vital and others , ), antihypertensive properties (Hernández‐Alvarez and others 2013; Rui and others ; Boschin and others ), antioxidant capacity (Valdez Ortiz and others ; Betancur‐Ancona and others 2014; Guzmán‐Méndez and others ); and antifungal activity (Wu and others ; Chan and others ; Wong and others ; Chan and Ng ). However, the novelty of this scientific research was to discover, for the 1st time, the biological potential of peptides from commercially precooked common bean hydrolysates on enzymes related to type‐2 diabetes as DPP‐IV as well as provide information about functional properties of commercially available processed products.…”
Section: Introductionmentioning
confidence: 99%